D is the only x-intercept out of the options listed below.
In order to find an x-intercept, you need a value that will cause the y-value to equal 0, since this is where x-intercepts exist.
Automatically, A and B do not work since the y-values in the ordered pairs do not equal 0. By definition they are not x-intercepts. Next we can try the x-values in the equation to see which gives us a 0 y-value.
C
f(x) = (x + 6)(x - 3)
f(6) = (6 + 6)(6 - 3)
f(6) = (12)(3)
f(6) = 36
Since this does not equal 0, it is not an x-intercept.
D
f(x) = (x + 6)(x - 3)
f(-6) = (-6 + 6)(-6 - 3)
f(-6) = (0)(-9)
f(-6) = 0
This shows us that D yields a 0 value for y and is thus a x-intercept.